Solve by using Quadratic Formula

please message ,correcting the question...

i think something is wrong in the question, i think the equation is

(3y-1)(y-1) = (5y - 3)(2y - 3)

i will solve this .....

(3y + 1)(y-1) = (5y - 3)(2y - 3)

3y^2 - 3y + y - 1 = 10 y^2 - 15y - 6y +9

7y ^2 - 19 y +10 = 0

then apply quadratic formula,

y = - b + or - √(b^2 - 4 a c) / 2a

= (19 + or - √ (361 - 4* 7*10))/2* 7

= (19 + 9 )/14 or (19 -9)/14

= 2 or 5/ 7............................

ANSWER IS y = 2 or 5/7..........

hope you understood...........please message if you have any doubts....thank you

i had solved taking equation as

(3y +1)(y-1) = (5y - 3)(2y - 3)..............................................

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up